ANALISIS PEMASARAN TELUR DI KECAMATAN TILATANG KAMANG KABUPATEN AGAM (Studi Kasus Peternakan H. Djarasun Mangkuto Kec. Tilatang Kamang Kabupaten Agam) - Rahmat Syafriardi; Ismet Iskandar (Universitas Andalas, 2006)
This research is aimed to identify marketing policy and and future startegy that should be taken by the business of H. Djarasun chicken husbandry.this husbandry is being chosen because this husbandry is the biggest husbandry in Kecamatan Tilatang Kamang, Kabupaten agam. In this research the writers collected primary data taken from the key informan in the business and secondary data which is taken from related government instituion.From this research the writers can formulated marketing strategy which is recommended to be held by the company.The startegy is optimizing the company resources and optimizing current market and supported with developing feed milling unit in the company to get lower cost, and optimizing the relationship with their current customers.